2018
DOI: 10.1371/journal.pone.0195567
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of the effects of older adult care dependence upon household economic functioning, in Peru, Mexico and China

Abstract: BackgroundWhile links between disability and poverty are well established, there have been few longitudinal studies to clarify direction of causality, particularly among older adults in low and middle income countries. We aimed to study the effect of care dependence among older adult residents on the economic functioning of their households, in catchment area survey sites in Peru, Mexico and China.MethodsHouseholds were classified from the evolution of the needs for care of older residents, over two previous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Since the life expectancy of women is higher than men in India, it may pose the women a higher risk of ailments and resultant hospitalisation. The studies have reported that household size is associated with the access to inpatient health care services [35][36][37]. Our ndings also indicate that elderly in small family utilise more inpatient health services than the household with big family size.…”
Section: Discussionsupporting
confidence: 56%
“…Since the life expectancy of women is higher than men in India, it may pose the women a higher risk of ailments and resultant hospitalisation. The studies have reported that household size is associated with the access to inpatient health care services [35][36][37]. Our ndings also indicate that elderly in small family utilise more inpatient health services than the household with big family size.…”
Section: Discussionsupporting
confidence: 56%
“…The INDEP study was designed to investigate earlier 10/66 findings in more depth across four sites: using mixed methods to explore the social and economic effects of caring for dependent older relatives, comparing outcomes among households with older residents needing care with those with independent older residents [ 48 ]. Results demonstrated that managing older people’s needs for care had adverse effects upon household economies, including lower paid income, lower consumption and increased healthcare expenditure (including more frequent catastrophic healthcare spending) among care households [ 52 ]. Qualitative results revealed the enduring intergenerational financial connectedness of households against a backdrop of changing demands upon family income and resulting strain: e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Without effective government support, families pieced together the care of older relatives, a task made all the more challenging by the inherent uncertainty of future demands [ 53 ]. As reflected in quantitative findings, this often had serious adverse consequences for the household as a whole, including restriction of healthcare use and food consumption [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…At an individual level, dependence can generate feelings of depression, low self-esteem, and hopelessness ( 6 ). At the level of family, it can generate a cycle of impoverishment and reallocation of care roles ( 7 ), while at the societal level, dependence can increase demand for health and care services ( 8 ). This increase demand for health and care services can also increase the costs associated with healthcare of dependent older people.…”
Section: Introductionmentioning
confidence: 99%